Multisensory Experience Dimensions, Experiential Satisfaction, and Revisit Intention: A Stimulus–Organism–Response Approach - Andry Herawati; Sarwani Sarwani; Liling Listyawati; Sandra Oktaviana; Galuh Ajeng Ayuningtiyas; Salsabila Deka Putri; Rischa Ardyanti (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the influence of multisensory marketing on tourist behavior within the Stimulus–Organism–Response (S-O-R) framework by analyzing five sensory dimensions: sight, sound, smell, taste, and touch. This topic is important because sensory experiences are increasingly used in tourism marketing to enhance visitor satisfaction and encourage revisit intentions, particularly in educational tourism destinations. Design/methodology/approach – This study employed a mixed-methods approach. Quantitative data were collected from 150 visitors to an educational tourism destination and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Qualitative insights were also incorporated to support and enrich the interpretation of quantitative findings. Findings/Results – The findings indicate that multisensory marketing influences tourist responses selectively rather than uniformly. Sight had a significant direct effect on revisit intention, whereas sound and touch significantly affected experiential satisfaction. Furthermore, experiential satisfaction has the strongest influence on revisit intention, confirming its important mediating role in the S-O-R framework. These results suggest that not all sensory dimensions contribute equally to the behavioral outcomes of tourists. Originality/Value – This study contributes to the sensory marketing literature by demonstrating the differential effects of sensory stimuli on tourists’ behavior. This study also extends the S-O-R framework by integrating direct and mediated relationships between sensory dimensions, experiential satisfaction, and revisit intention. The main implication is that tourism managers should prioritize the most influential sensory dimensions to create more effective visitor experiences and strengthen their loyalty.